SalFSAR: A Dual Purpose Device for Laparoscopic Training and Tele-Surgery - Salleh, Rosli; Razak, Zaidi; Caldwell, Darwin; Loureiro, Rui (Malaysian Journal of Computer Science, 2005)
This paper presents the design of the Salford Laparoscopic Feedback Simulators and Robot (SalFSAR). It is designed as a dual-purpose device i.e. as a laparoscopic manipulator for virtual reality (VR) simulation and also as a surgical robot. A VR environment has been developed to test the applicability of the device for assisting surgeons in laparoscopic surgery procedures.